Semantic differences between enantiosemy and antonymy in English and Uzbek - Hafizov , Sarvar Boborajab ugli (The Lingua Spectrum, 2026)
This article examines a question that is often oversimplified in descriptive semantics: Are enantiosemy and antonymy two variants of the same opposition, or do they represent different mechanisms of semantic organization? The research material consists, on the one hand, of canonical antonymic pairs in English and Uzbek, and on the other, of a purposefully selected comparative set of enantiosemic units from English and Uzbek sources. Methodologically, the study combines comparative-semantic analysis, contextual analysis, elements of a corpus-oriented approach, and descriptive quantification. The focus is not only on dictionary definitions but also on how opposing meanings are distributed across contexts, syntactic frames, and evaluative speech modes. The study shows that antonymy constitutes an interlexical, largely binary, and typically decontextualizable opposition, whereas enantiosemy is localized within a single form, depends much more heavily on context, and often exhibits asymmetry between opposing meanings. For English material, the most characteristic examples are lexically fixed terms such as sanction, oversight, dust, seed, clip, graduate, and solicitor; for the Uzbek material-not only lexical, but also grammatical, phraseological, and subjective-evaluative realizations, for example, toʻychi, tushmoq, chiqmoq, olmoq, yuz burmoq, as well as the literary usages of ofat and qiyomat. On this basis, it is demonstrated that enantiosemy cannot be reduced to either “internal antonymy” or ordinary polysemy: it is a special type of sign-internal opposition situated at the intersection of lexical semantics, pragmatics, and the historical development of meaning.